Role of Chemical Components of cork on Sorption of Aqueous Polycyclic Aromatic Hydrocarbons - Environ, J. (International Journal of Environmental Research, 2013)
In order to know the environmental behaviour of toxic pollutants it is fundamental to understand the role of chemical components of a material on sorption of such pollutants.In this study, the sorption of a mix of polycyclic aromatic hydrocarbons (PAHs) by cork fractions (i.e. raw cork (CF), free extractive cork (FEF) and nonsaponifiable (DESF)) has been investigated to better understand the role of biopolymers and extractable fraction of cork on their sorption behaviour. All samples were analyzed through elemental analysis and were examined using Fourier transform infrared spectroscopy. After removing the extractable fraction and the suberin from the cork, the sorption capacities (Koc ) of FEF and DESF exhibited mean reductions of 70% and 30% respectively. In addition, the sorption results of three pairs of cork samples with different chemical content confirm that the extractable fraction serves as the major sorption medium for PAHs. Considering only low molecular weight PAHs positive correlations between Koc with Kow (R2 =0.70) and F number (R2 =0.65) were found, showing that these parameters are involved in this adsorption process
Keywords: biopolymers; Cork; extractable fraction; organic pollutants; PAHs